The Synergy cementless femoral stem in primary total hip arthroplasty at a minimum follow-up of 15 years. Issue 1 (January 2017) - Martino, I. De; Santis, V. De; Apolito, R. D'; Sculco, P. K.; Cross, M. B.; Gasparini, G.
Abstract : Aims: We report on the outcome of the Synergy cementless femoral stem with a minimum follow-up of 15 years (15 to 17). Patients and Methods: A retrospective review was undertaken of a consecutive series of 112 routine primary cementless total hip arthroplasties (THAs) in 102 patients (112 hips). There were 60 female and 42 male patients with a mean age of 61 years (18 to 82) at the time of surgery. A total of 78 hips in the 69 patients remain in situ ; nine hips in eight patients died before 15 years, and 16 hips in 16 patients were revised. Clinical outcome scores and radiographs were available for 94 hips in 85 patients. Results: In all, four stems were revised. One stem was revised for aseptic loosening; two stems because of deep infection; and one because of periprosthetic femoral fracture. There was a significant improvement in all components of the Western Ontario and McMaster Universities Osteoarthritis Index score at the final follow-up (total: p < 0.001, pain: p < 0.001, stiffness: p < 0.001, function: p < 0.001). The mean Harris Hip Scores improved from 47 points (27 to 59) pre-operatively to 89 points (65 to 100) at the latest follow-up (p < 0.001). Kaplan-Meier survivorship, with stem revision for aseptic loosening as the endpoint, was 98.9% at 15 years (95% confidence interval (CI) 96.9 to 100, number at risk at 15 years: 90) and with stem revision for any reason was 95.7% (95% CI 91.7 to 99.8, number at risk at 15 years: 90). Conclusion: The Synergy cementless femoral stem demonstrates excellent survivorship and functional outcomes at 15 years. Cite this article: Bone Joint J 2017;99-B:29–36.